2014
DOI: 10.1093/intqhc/mzu036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of regulatory bodies in managing health professional issues and errors in Europe

Abstract: There is little consistency across Europe on the regulation of medical professionals. There is considerable diversity in the range of topics that regulatory bodies oversee, with almost all covering health care quality and safety and others encompassing issues related to reputation, respect and trust. These inconsistencies have significant implications for professional mobility, patient safety and quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…5 Under the new legislation, member states will have to establish an 'alert system' to warn each other within 3 days when a health professional is banned or his or her practice restricted, even temporarily. This is a signifi cant improvement on the current situation whereby 'rogue' professionals can continue to practice by slipping across national borders, but the devil will be in the detail of this legislation.…”
Section: Warning Systemmentioning
confidence: 99%
“…5 Under the new legislation, member states will have to establish an 'alert system' to warn each other within 3 days when a health professional is banned or his or her practice restricted, even temporarily. This is a signifi cant improvement on the current situation whereby 'rogue' professionals can continue to practice by slipping across national borders, but the devil will be in the detail of this legislation.…”
Section: Warning Systemmentioning
confidence: 99%
“…Findings of the study showed that the field visits are performed both announced and unannounced. In most monitoring systems scheduled monitoring is performed at regular intervals or at least annually (37); in addition, unannounced visits are made to investigate complaints.…”
Section: Discussionmentioning
confidence: 99%
“…External inspection standards in healthcare varies between investigating organisational behaviour, healthcare professionals or estimating patient outcomes, but Flodgren et al argue in their systematic review that there is too few studies in this field to draw a conclusion about the effectiveness of the external inspections [31]. According Risso-Gill et al [32], there is limited consistency across Europe on the regulation of medical professionals, and there is variation in the range of topics that the regulatory bodies oversee. But, almost all regulatory bodies follow up healthcare quality and safety, and topics related to trust, respect and reputation [32].…”
Section: Discussionmentioning
confidence: 99%
“…According Risso-Gill et al [32], there is limited consistency across Europe on the regulation of medical professionals, and there is variation in the range of topics that the regulatory bodies oversee. But, almost all regulatory bodies follow up healthcare quality and safety, and topics related to trust, respect and reputation [32]. Moreover, there is variation across Europe in the targets of the inspections and whether or not inspections focus mainly on the organization and management or on the healthcare professionals [24].…”
Section: Discussionmentioning
confidence: 99%